2012
DOI: 10.1080/15287394.2012.699846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1800-MHz Radiofrequency Fields on Circadian Rhythm of Plasma Melatonin and Testosterone in Male Rats

Abstract: Radiofrequency fields (RF) at 1800 MHz are known to affect melatonin (MEL) and testosterone in male rats, but it remains to be determined whether RF affected circadian rhythm of these plasma hormones. Male Sprague-Dawley rats were exposed to 1800-MHz RF at 208 μw/cm² power density (SAR: 0.5762 W/kg) at different zeitgeber (ZT) periods of the day, including 0 (ZT0), 4 (ZT4), 8 (ZT8), 12 (ZT12), 16 (ZT16), and 20 (ZT20) h. RF exposure was 2 h/d for 32 d. From each rat, the concentrations of plasma MEL and testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
3
14
0
1
Order By: Relevance
“…In a previous study, we reported a robust circadian rhythm for testosterone in rat blood plasma, together with an inverse phase pattern compared to melatonin (Qin et al, 2012). In the present study, the levels of testosterone in the testes were also found to fluctuate with time, with a peak at ZT 01:34.…”
Section: Discussionsupporting
confidence: 49%
“…In a previous study, we reported a robust circadian rhythm for testosterone in rat blood plasma, together with an inverse phase pattern compared to melatonin (Qin et al, 2012). In the present study, the levels of testosterone in the testes were also found to fluctuate with time, with a peak at ZT 01:34.…”
Section: Discussionsupporting
confidence: 49%
“…EMR in the range of 100 kHz-300 GHz is becoming more widespread and extensively employed in both the urban and rural environment, attributed to increasing use of radio and TV appliances, of radar units, and especially of mobile phones and wireless communication devices (Valberg et al, 2007). EMR was shown to induce damage in different organs, including the reproductive system, heart, lungs, kidney, testes, and liver (Fernie and Reynolds, 2005;Hanafy et al, 2010;Qin et al, 2012;Shahrbanoo et al, 2013;Almášiová et al, 2014), and affected negatively the motility of spermatozoa (Lukac et al, 2011). The aim of this study was to determine the potential adverse effects of EMR on the structure and ultrastructure of rat liver.…”
Section: Mobile Communication Systems Are Undoubtedly An Environmentamentioning
confidence: 98%
“…In mammals, melatonin is synthesized by the pineal gland during the dark phase, and plays an important role in physiologic and reproductive activities (Lanoix et al, 2008;Lincoln et al, 2003). An inverse relationship between melatonin synthesis and testosterone levels has previously been reported (Qin et al, 2012), with an assumption of both indirect and direct mechanisms. For the former, it is hypothesized to be manifested through the hypothalamo-hypophysial-gonadal axis by altering gonadotrophin-releasing hormone (GnRH)-induced luteinizing hormone release from the anterior pituitary gland (Hattori et al, 1995;McGuire et al, 2011;Sirotkin and Schaeffer, 1997;Vanecek, 1999).…”
Section: Introductionmentioning
confidence: 98%